The Interactive Urban Model: Histories and Legacies Related to Prototyping the Twenty-First Century City - Verebes, Tom (Frontiers in Digital Humanities, 2016)
This article surveys the theoretical and historical legacies of mass production and standardization, and the cultural issues associated with globalization, in the most prolific era ever of urbanization. Situated at the intersection of scholarly writing on history, current conditions, and a speculative future, this article focuses on themes related to design research on computation, fabrication, and the city. Given the ongoing transition of industrial paradigm from Modernism’s dependency upon Fordist mass production, the context of today’s emerging methods of non-standard production is explored, with an emphasis on design repercussions at the urban scale. Theorizations of the cultures surrounding, within, and against technology, this article will confront the difficult issues of the expression of identity in late capitalism, through resistance of regionalism and other neo-traditionalist positions in an increasingly globalized world. These issues lead to a proposition of the notion of an interactive urban model, as the basis of embedding intelligence into city design, and the potential of producing highly customized materialization through contemporary production technologies. The hypotheses of these issues are explicated by three case study design projects, carried out by the author’s practice, OCEAN CN Consultancy Network, based in Hong Kong. The three projects demonstrate the author’s design research experimentation with design and production technologies at various scales of practice in architecture, urbanism, urban and landscape design, and masterplanning, applying computation toward the objective of achieving, modulated spatial attributes.